Factors Associated with Return of Spontaneous Circulation following Pre-Hospital Cardiac Arrest in Daegu Metropolitan City, South Korea; a Cross-Sectional Study - Jung, Hyun-Ok; Han, Seung-Woo (Archives of Academic Emergency Medicine, 2022)
Introduction: The probability of Return of Spontaneous Circulation (ROSC) in cardiac arrest cases in pre-hospital setting is still low. This study aimed to identify the factors that may improve the rate of ROSC in patients with pre-hospital cardiac arrest. Methods: This retrospective cross-sectional study is a secondary data analysis of cardiac arrest patients, who were managed by paramedics in the pre-hospital setting, from January 1, 2019, to December 31, 2019, in Daegu, South Korea. The association of ROSC with place of arrest occurrence, cardiac arrest being witnessed, performing cardiopulmonary resuscitation (CPR), using compression device and defibrillator, administration of epinephrine, and intubation was analyzed and independent predictive factors of ROSC were reported. Results: 2750 out-of-hospital cardiac arrest cases, which were managed by paramedics in the pre-hospital setting were studied. 2034 (86.9%) cases of arrest had occurred at home, 2028 (73.7%) were not witnessed, and CPR was not performed for 1721 (64.1%) cases. ROSC before arriving to emergency department (ED) was more probable if the cardiac arrest was witnessed (p < 0.001), if CPR was performed (p = 0.044), if a mechanical compression device was used (p < 0.001), if a first-aid defibrillator was used (p < 0.001), and if intravenous access was secured (p < 0.001). Multivariate regression analysis revealed that using mechanical compression device (OR: 0.18; 95% CI = 0.08 - 0.40; p = 0.001), using first-aid defibrillator (OR: 3.13; 95% CI = 1.40 - 6.99; p = 0.005), administration of epinephrine (OR: 6.57; 95% CI = 2.16 - 19.53; p = 0.001), and intubation (OR: 1.82; 95% CI = 1.04-3.19; p = 0.001) were independent predictive factors of ROSC before arrival to ED. Conclusion: It seems that chest compression by hand instead of using chest compression device, using defibrillator, epinephrine administration, and intubation my increase the probability of ROSC in pre-hospital arrest cases.